2020
DOI: 10.1111/apt.16204
|View full text |Cite
|
Sign up to set email alerts
|

Fructan‐sensitive children with irritable bowel syndrome have distinct gut microbiome signatures

Abstract: SummaryBackgroundDietary fructans may worsen gastrointestinal symptoms in children with irritable bowel syndrome (IBS).AimTo determine whether gut microbiome composition and function are associated with childhood IBS fructan‐induced symptoms.MethodsFaecal samples were collected from 38 children aged 7‐17 years with paediatric Rome III IBS, who previously completied a double‐blind, randomised, placebo‐controlled crossover (fructan vs maltodextrin) trial. Fructan sensitivity was defined as an increase of ≥30% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 63 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Oduaran et al (2020) analyzed the population of South Africa and observed a significant abundance of the Vampirovibrio members (non-photosynthetic cyanobacterial Melainabacteria) in the rural community Bushbuckridge when compared to inhabitants the highly urbanized area Soweto [37]. Chumpitazi et al (2019) noticed that the fructan-sensitive children with irritable bowel syndrome have enriched cyanobacteria compared to the fructan-tolerant group, indicating the involvement of cyanobacteria in food digestion [38]. Cai et al (2020) analyzed the gut microbiota composition in the patients with Wilson's disease (an autosomal recessive inherited disorder of chronic copper toxicosis), and they observed a higher cyanobacterial abundance in the patients with Wilson's disease compared to the health controls (0.12% vs. 0.0%, p < 0.05) [39].…”
Section: Gastrointestinal and Metabolic Diseasesmentioning
confidence: 99%
“…Oduaran et al (2020) analyzed the population of South Africa and observed a significant abundance of the Vampirovibrio members (non-photosynthetic cyanobacterial Melainabacteria) in the rural community Bushbuckridge when compared to inhabitants the highly urbanized area Soweto [37]. Chumpitazi et al (2019) noticed that the fructan-sensitive children with irritable bowel syndrome have enriched cyanobacteria compared to the fructan-tolerant group, indicating the involvement of cyanobacteria in food digestion [38]. Cai et al (2020) analyzed the gut microbiota composition in the patients with Wilson's disease (an autosomal recessive inherited disorder of chronic copper toxicosis), and they observed a higher cyanobacterial abundance in the patients with Wilson's disease compared to the health controls (0.12% vs. 0.0%, p < 0.05) [39].…”
Section: Gastrointestinal and Metabolic Diseasesmentioning
confidence: 99%
“…Recently, the same authors tried to provide a biomarker of response to a low‐FODMAP diet by profiling fecal microbiota in children with IBS through a cross over provocation using fructans (a FODMAP) and maltodextrin (placebo) solutions (48). Those classified as ‘fructan‐sensitive’ differed in their fecal microbiota on alpha diversity, and abundances of Holdermania and 14 Clostridial genera from those deemed ‘fructan‐tolerant’.…”
Section: Microbiota Implications Of the Low‐fodmap Diet In Pediatric ...mentioning
confidence: 99%
“…This study demonstrated a higher abundance of Cyanobacteria in infants with viral diarrhea compared to healthy individuals [48]. In fecal samples from 38 children aged 7-17 years with pediatric Roman type III IBD who had previously completed a doubleblind, randomized, placebo-controlled crossover trial (fructose versus maltodextrin), an elevated abundance of Cyanobacteria was observed after fructan ingestion compared to fructan-tolerant children [49]. These studies suggest a potential involvement of Cyanobacteria in the development of gastrointestinal and inflammatory diseases, though further research is needed to determine whether intestinal Cyanobacteria can cause diseases or whether changes in their abundance are a consequence of disease.…”
Section: Discussionmentioning
confidence: 63%